2005
DOI: 10.1007/s10024-005-8089-z
|View full text |Cite
|
Sign up to set email alerts
|

Nonimmune Hydrops Fetalis in the Liveborn: Series of 32 Autopsies

Abstract: Nonimmune hydrops fetalis (NIHF) or generalized soft tissue edema and cavity effusions may be due to cardiovascular diseases, congenital infections, genitourinary malformations, thoracic masses, placental conditions, chromosomal abnormalities, and idiopathic. We report 32 cases of NIHF from among 429 neonates who underwent autopsies (incidence 7.45%). Sixteen cases (50%) had cardiovascular disease; all were due to low output cardiac failure; 7 had structural congenital heart disease. Three of the children with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…The combination of examination of the fetus and placenta with the results of microbiological, cytogenetic and metabolic investigations provides an etiological diagnosis for non-immune fetal hydrops in 65-85% cases in various previous studies. 11,12 The low diagnostic yield in hydrops fetalis in this study is possibly due to incomplete investigative workup for infective and metabolic disorders.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The combination of examination of the fetus and placenta with the results of microbiological, cytogenetic and metabolic investigations provides an etiological diagnosis for non-immune fetal hydrops in 65-85% cases in various previous studies. 11,12 The low diagnostic yield in hydrops fetalis in this study is possibly due to incomplete investigative workup for infective and metabolic disorders.…”
Section: Discussionmentioning
confidence: 89%
“…11 Structural cardiac anomalies, abnormalities of the rhythm and cardiomyopathies have been reported to account for about 50% of cases. 12 The other common causes of hydrops are chromosomal (5-33%) and infections (12-16%). 13,14 Congenital malformations, fetal akinesia syndromes and skeletal dysplasias are also reported with fetal hydrops.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of cases of HF are due to cardiovascular, chromosomal, thoracic, twinning or anemic causes [Heinonen et al, 2000;Rodriguez et al, 2005]. The etiology in the other third of cases is unknown [Machin, 1989].…”
Section: Discussionmentioning
confidence: 97%
“…In fact, B19 infection was the fifth most prevalent of a total of 23 individually classified NIFH aetiologies by these authors. Subsequently, Rodriguez et al (2005) have also studied the aetiology of NIFH in liveborn infants (n ¼ 429, 14-year period) who died soon after birth. Although a similar incidence of NIFH was observed to the previous study (7.45%; 32/429), the aetiology of B19-associated NIFH, in an individual with systemic infection and myocarditis, was only 3.1% (1/32 cases).…”
Section: Successfulmentioning
confidence: 99%
“…These authors have suggested that revision of current follow-up criteria may be necessary if extended viraemia is a more common occurrence than heretofore thought. Rodriguez et al (2002Rodriguez et al ( , 2005 have undertaken the analysis of NIFH in both stillborn and livebirth autopsy scenarios. Following the evaluation of 840 stillborn autopsies (Rodriguez et al, 2002), 51 cases of NIFH were observed which represented 6.07% of all stillbirths.…”
Section: Successfulmentioning
confidence: 99%